Surgical options in the treatment of oroantral fistula / communication: Case series (Research, Society and Development, 2020)
Purpose: to report three cases of fistula and one case of oroantral communication with different treatment proposals based on clinical characteristic of each patient, as well as to discuss possible techniques used in this pathological condition. Method: a search for scientific articles was done out in the Pubmed and SciELO databases for scientific basis and construction of clinical case reports. Results and Conclusions: surgical procedures to close communications or oroantral fistulas are necessary interventions and should be performed as soon as possible. The choice of surgical technique must be made individually for each patient, for correction of bone defect aiming the resolution of infectious process and clinical complaints.